Auto-immune encephalitis as differential diagnosis of infectious encephalitis - Armangue, Thaís (2014)
PURPOSE OF REVIEW: To describe the main types of autoimmune encephalitis with special emphasis on those associated with antibodies against neuronal cell surface or synaptic proteins, and the differential diagnosis with infectious encephalitis. RECENT FINDINGS: There is a continuous expansion of the number of cell surface or synaptic proteins that are targets of autoimmunity. The most recently identified include the mGluR5, DPPX, and the GABA(A)R. In these and previously known autoimmune encephalitis (NMDAR, AMPAR, GABA(B)R, LGI1, CASPR2), the prodromal symptoms or types of presentations often suggest a viral encephalitis. We review here clues that help in the differential diagnosis with infectious encephalitis. Moreover, recent investigations indicate that viral encephalitis (e.g., herpes simplex) can trigger synaptic autoimmunity. In all these disorders immunotherapy is usually effective. SUMMARY: Autoimmune encephalitis comprises an expanding group of potentially treatable disorders that should be included in the differential diagnosis of any type of encephalitis.